Analisis peran guru penggerak sebagai pendorong komunitas belajar serta diskusi kolaborasi pada kurikulum merdeka di sekolah dasar - Muhammad Hanif Amril Putra; Sri Marmoah (Didaktika Dwija Indria, 2025)
This study aims to analyze the role of motivational teachers in the independentcurriculum at Ta'mirul Islam Elementary School in Surakarta. This study uses a qualitativeapproach with a case study research type. The sources of data for this study include twomotivational teachers, one principal, and one colleague. The sampling technique used waspurposive sampling. Data collection was conducted through observation, interviews, anddocumentation. The validity test technique used was triangulation of techniques and sources.The data analysis technique used interactive analysis. The results of the study show thatmotivational teachers have five main roles. However, in this article, the author takes only tworoles, namely motivating the learning community both within the school and between schoolsand opening up space for positive discussion and collaboration with teachers, parents, andexternal stakeholders. This study confirms that Motivational Teachers play a strategic role asagents of change in supporting the successful implementation of the Merdeka Curriculum, whichis relevant to current educational needs and contributes to building an adaptive, collaborativelearning environment oriented towards the Pancasila Student Profile.